Prospective Multicenter Randomized Controlled Trial Comparing Early Protected Movement and Splinting for Fifth Metacarpal Neck Fracture. Issue 1 (February 2022) - Retrouvey, Helene; Jakubowski, Josephine; Al-Taha, Mona; Steve, Anna; Augustine, Haley; Stein, Michael J.; Al-Halabi, Becher; Efanov, Johnny Ionut; Morzycki, Alexander; Tang, David; LeBlanc, Martin; Binhammer, Paul; et al.
Background: Fifth metacarpal neck fractures account for 20% of all hand fractures, yet there remains debate with respect to management, particularly when conservative treatment is initiated. The objective of this study is to compare functional and patient-reported outcomes (PROs) in patients treated with early protected movement or splint immobilization. Methods: This national multicenter prospective randomized controlled trial compared 2 groups; elastic bandage with early protected movement versus immobilization with splinting. Demographic characteristics were collected at baseline. Functional outcomes (grip strength testing) and PROs (Brief Michigan Hand Questionnaire [bMHQ]) were collected at 4, 8, and 12 weeks post-intervention. Grip strength values of the injured hand were normalized to both the non-injured hand (at baseline), and the Canadian reference values. Results: Thirty-seven participants from 5 Canadian centers were randomized into the splint (n = 21) or elastic bandage group (n = 16). There were no significant differences in the bMHQ score between the splint (52.1 ± 27.2) or the elastic bandage (46.6 ± 20.4) groups ( P = .51). There were no differences in baseline grip strength between the splint (15.3 ± 8.9 kg) and elastic bandage (19.9 ± 7.5 kg) groups. At 8 weeks, the elastic bandage group had a significantly higher grip strength than the splint group (93% vs 64%, respectively: P < .05), when standardized as a percentage of the Canadian reference values. Conclusion: Patients with Boxer's fractures treated with early protected movement had better functional outcomes by 8 weeks post-treatment as compared to the Canadian reference values of those treated with immobilization and splinting. Providers should manage Boxer's fractures with early protected movement.